Pengaruh Antibakteri Kombinasi Ekstrak Kulit Jeruk Manis (Citrus Sinensis (L.) Osbeck) dan Daun Pepaya (Carica Papaya L.) Terhadap Bakteri Escherichia Coli - Regitha Adiba Fayza Purwoko; Riana Putri Rahmawati; Muhammad Khudzaifi (Pusat Riset dan Inovasi Nasional, 2025)
Sweet orange peel and papaya leaves have been used by the community to prevent and treat various diseases caused by bacterial, fungal, and viral infections. Sweet orange peel contains flavonoids, alkaloids, saponins, tannins, and terpenoids that can inhibit bacterial growth. While papaya leaves contain active compounds such as alkaloids, flavonoids, steroids, tannins, and terpenoids that can inhibit bacterial growth. Escherichia coli bacteria are gram-negative, facultative anaerobic bacteria that can cause intestinal infections, causing diarrhea. The combination of extracts from several plants has greater inhibitory power so that it has greater antibacterial activity than a single plant. The purpose of this study was to determine whether the combination of sweet orange peel and papaya leaf extracts has an effect on the growth of Escherichia coli bacteria. The test method used was the disc diffusion method on TSA agar media. Sweet orange peel and papaya leaf extracts in this study were obtained by the maceration method with 96% ethanol solvent. The ratio of extracts used was sweet orange peel and papaya leaves 1:3; 2:2; 3:1. The positive control used was ciprofloxacin. The negative control used was 10% dimethyl sulfoxide (DMSO). The results of this study indicate that the combination of sweet orange peel extract (Citrus sinensis L. Osbeck) and papaya leaves (Carica papaya L.) has an effect on the growth of Escherichia coli bacteria because it produces an inhibition zone around the disc paper. All comparisons, namely 1: 3; 2: 2; 3: 1 are optimal in inhibiting the growth of Escherichia coli bacteria with a diameter of the inhibition zone in sequence of 17.78 mm (strong category), 22.14 mm (very strong category), and 26.28 mm (very strong category). Likewise, the positive control produces an inhibition zone of 34.25 (very strong category). The most optimum antibacterial combination shows the diameter of the inhibition zone against Escherichia coli bacteria, namely at a ratio of 3: 1.